Strategi Pemecahan Konflik Siswa Sekolah Dasar Di Kabupaten Bangkalan - Ernawati; Ana Yuliati (Penerbit STKIP PGRI Bangkalan, 2019)
The purpose of this research is to find out the causes of conflict, if the cause of conflictis known then the way to control conflict can be done by means of mutualisation,mediation, arbitration and control with peer mediation, so that conflicts can be resolvedcorrectly and appropriately in ways that are not harmful one of the parties, so thatthere is no hostility or violence caused by the conflict. The object of this study was theprincipal, teacher, and students of SDN Kemayoran 1 Bangkalan. The research methodused in this study is a qualitative research method using a descriptive approach toidentify factors that cause students to be involved in conflict in school and to find outhow schools handle conflicts that occur in elementary school students. To get theexpected data, researchers will collect data using two techniques, namely interviewtechniques and documentation techniques. The results of the study stated that the causeof the conflict in the form of ridicule of another student who led to a fight. The maincause is that no one wants to budge so there is a fight which results in a fight.